Optical pavement treatments and their impact on speed and lateral position at transition zones: A driving simulator study. (February 2021) - Hussain, Qinaat; Alhajyaseen, Wael K.M.; Reinolsmann, Nora; Brijs, Kris; Pirdavani, Ali; Wets, Geert; Brijs, Tom
Highlights: Road markings with gradual increase in size and/or brightness were used Highest speed reduction was observed for markings with the combined effects Drivers' lateral control was not negatively influenced due to the road markings Markings varying pattern-wise in brightness and size are recommended for transition zones Abstract: Transition zones are a road section where posted speed drops from higher to lower limits. Due to the sudden changes in posted speed limits and road environment, drivers usually do not adapt to the posted speed limits and underestimate their traveling speed. Previous studies have highlighted that crash rates are usually higher in these sections. This study aims at improving the safety at transition zones by introducing perceptual measures that are tested using a driving simulator. The proposed measures are speed limit pavement markings with a gradual increase of brightness and/or size that were placed at transition zones in simulation scenarios replicating the real-world environment of the Doha Expressway in Qatar. These innovative measures aim to produce the impression of increased speed that could stimulate drivers to better adapt speed limits. The driving behavior of 81 drivers possessing a valid Qatari driving license was recorded with a driving simulator interfaced with STISIM Drive® 3. Results showed that pavement markings combining size and brightness manipulations were the most effective treatment, keeping drivers' traveling speed significantly below the traveling speed recorded in the untreated control condition. In this regard, the maximum mean speed reductions of 5.3 km/h and 4.6 km/h were observed for this treatment at the first transition (120 to 100 km/h) and second transition (100 to 80 km/h) zones, respectively. Regarding the variations in drivers' lateral position, the results showed that the proposed pavement markings did not negatively influence drivers' lateral control on the road as the maximum observed standard deviation of lateral position was around 0.065 m. This study shows that the proposed pavement markings are recommended for improving the speed adaptation of drivers in the transition zones.